Mineral Water Versus Demineralized Water: A Comparative Review Based On Scientific Evidence Of Composition And Health Benefits - Sihombing, Pardomuan Robinson (Jurnal Ilmiah Kesehatan Pernus, 2025)
The consumption of bottled drinking water (BDW) shows a significant upward trend globally, but is accompanied by public confusion regarding the fundamental differences between the various types of products available, especially mineral water and demineralized water. This study aims to conduct a comparative analysis based on scientific evidence of the two types of water. Using a systematic literature review of indexed primary research articles, this study examines the differences in definition, production process, chemical composition, and implications for human health. The analysis shows that mineral water, with its natural mineral content, calcium, and magnesium, significantly benefits bone and cardiovascular health. Conversely, long-term consumption of demineralized water is not recommended for the general population because it risks causing electrolyte imbalances and leaching essential nutrients from food during cooking. The optimal choice of water type is proven to be highly dependent on individual physiological contexts; mineral water is ideal for daily hydration and athlete recovery, while demineralized water has a crucial role in specific medical applications such as hemodialysis and has the potential to reduce the risk of kidney stones in susceptible individuals. It is concluded that mineral water is a physiologically superior choice for daily consumption by the general public. Better public education is needed to improve consumer understanding in choosing drinking water that suits their health needs